Follow‐up of the Cool Little Kids translational trial into middle childhood. (15th June 2021) - Bayer, Jordana K.; Brown, Amy; Prendergast, Luke A.; Bretherton, Lesley; Hiscock, Harriet; Mihalopoulos, Cathrine; Nelson‐Lowe, Margaret; Gilbertson, Tamsyn; Noone, Kate; Bischof, Natalie; Beechey, Cassima; Muliadi, Fenny; et al.
Abstract : Background: Public health advocates have highlighted internalising problems as a leading cause of global burden of disease. Internalising problems (anxiety/depression) affect up to 20% of school‐age children and can impact peer relations, school engagement and later employment and mortality. This translational trial aimed to determine whether a selective/indicated parenting group programme to prevent internalising distress in shy/inhibited preschool children had sustained effects in middle childhood. Translational design aspects were a brief parent‐report screening tool for child inhibition offered universally across the population via preschools in the year before school, followed by an invitation to parents of all inhibited children to attend the parenting programme at venues in their local community. Methods: Design of the study was a randomised controlled trial. The setting was 307 preschool services across eight socioeconomically diverse government areas in Melbourne, Australia. Participants were 545 parents of inhibited four‐year‐old children of which 456 (84%) were retained during middle childhood (age of seven to 10 years). Early intervention was the Cool Little Kids parenting group programme, and control was 'usual care' access to available support services in the community. Primary outcomes were child anxiety and depression symptoms (parent and child report) and DSM‐IV anxiety disorders (assessor masked). Secondary outcomes were parenting practices and parent mental health. Results: There was no significant difference in anxiety disorders between the intervention and control group during the three annual follow‐ups of the cohort in middle childhood (2015 43% vs. 41%, 2016 40% vs. 36%, 2017 27% vs. 30%, respectively; p 's > .05). There were also no significant differences in child anxiety or depression symptoms (by child or parent report), parenting practices or parent mental health, between the intervention and control group during middle childhood. However, a priori interaction tests suggested that for children with anxious parents, early intervention attenuated risk for middle childhood internalising problems. Conclusions: An issue for population translation is low levels of parent engagement in preventive interventions. Initial effects of the Cool Little Kids parenting group programme in reducing shy/inhibited preschool children's internalising distress at school entry dissipated over time, perhaps due to low engagement. Future translational research on early prevention of internalising problems could benefit from screening preschool children in the population at higher risk (combining temperamental inhibition and parent distress) and incorporating motivational techniques to facilitate family engagement. Trial registration ISRCTN30996662 http://www.isrctn.com/ISRCTN30996662 .